Analisis Putusan Pengadilan Agama Tanjung Karang No. 157/Pdt.G/2006/Pa.Tnk. Tentang Pembatalan Perkawinan (Studi Pada Pengadilan Agama Tanjung Karang) - Erlina B (PRANATA HUKUM, 2012)
As being live to continue its clan, hence there are relation both into marriage institute and with that marriage generateÂ law , that is event suaatu which in giving effect of by law by that because problem of marriage in our State is based on religion law and State law. Problems is What the reason of raising of application of cancellation of marriage, How consideration of judge in decision Justice Of Religion of Tanjungkarang Number 157/Pdt.G/2006/PA.Tnk, and How legal consequences cancellation of marriage in decision Justice of Religion Number 157 / Pdt.G / 2006 / PA.TNK. This Research use method approach of empiric and normatif, source of data of sekunder Data collecting primary data and done with bibliography study and field study and analysis qualitative.. Result of research of reason raising of application of cancellation of marriage is done nuptials between sued I and sued II there no permission of plaintiff, Consideration of judge is the nuptials null and void because of existence of forgery of identity by SuedÂ I with widower status, while SuedÂ I still has valid wife husband relation, with plaintiff. Besides SuedÂ I nor there is approval of valid wife ( Plaintiff), which is arranged in section 5 sentence ( 1), legal consequences cancellation of marriage its cancelation of marriage and Sued can raise other legal effort that is comparing.